Estilos de aprendizaje de estudiantes del 5° de secundaria de instituciones educativas estatal y particular del Callao Cercado - Ferrón Taipe, Cecilia Edelmira (2012)
The research aims to establish whether there were differences in learning styles among students in the 5th grade of secondary of the state and private educational institutions of the Fence Callao. The sample were of 100 students (79 of the state institution and 21 of the private institution). Questionnaire was used Honey - Alonso Learning Styles (CHAEA), comprising four learning styles: active, reflective, pragmatic and theoretical. The kind of research were basic, with a descriptive and comparative design. The results found do not exist big differences in the learning styles of students from of a state instituction and a private institution except in the active style with a very high preference in the students of the educational particular institution.